A Comparative Study of Students’ Vocabulary Mastery before and after Joining Epic English Course - Liem, Steven Salvator; Suryo, Arif (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the effectiveness of the Epic English Course in enhancing students’ vocabulary mastery. Using a quantitative pre-experimental design with a one-group pre-test and post-test approach, the research involved 30 students whose vocabulary performance was measured before and after participating in the course. The results showed a significant improvement, with the mean score increasing from 53.33 to 79.78, indicating an average gain of 26.45 points. Statistical analysis using a paired sample t-test revealed a t-value of -55.323 and a significance level of 0.000 (p 0.05), confirming the improvement was statistically significant. Moreover, the effect size, calculated using Cohen’s d, was 10.1, indicating a very large practical impact. The findings demonstrate that the Epic English Course, through its interactive, contextual, and student-centered approach, is highly effective in improving students’ vocabulary mastery and can serve as a valuable supplement to traditional classroom instruction.